Radiação solar ultravioleta e a fotoprodução de vitamina D in vitro em cidades do Nordeste e Sudeste do Brasil - Leal, Angela Cristina Gomes Borges [UNIFESP] (2020)
In order to compare the production of Vitamin D in different latitudes in Brazil, this in vitro experiment was carried out exposing glass ampoules containing vitamin D precursor (7-dehydrocholesterol) to sunlight. This model simulates human cutaneous production of vitamin D. This research was conducted concurrently in Fortaleza (latitude 3.7°S, 38.5°W, 27 m - LAT 3°S) and in São Paulo (23.5°S, 46.6°W, 760 m - LAT 23°S), exposing the ampoules to sunlight hourly from 7 a.m. to 5 p.m., one day per month, over a year. Following exposure, the vials had their content analyzed via High Performance Liquid Chromatography (HPLC) at the Vitamin D, Skin and Bone Research Laboratory at Boston University School of Medicine, which calculated the percentage conversion of 7-DHC to vitamin D3 and inactive derivatives. The analysis of the results obtained showed a greater seasonal variation in vitamin D production in LAT 23°S, while in LAT3°S the production was 19.7% higher and more stable over a year. The production corresponding to the beginning of conversion of Vitamin D in human skin could be detectable from 8 am on LAT 3°S throughout the year. However, during the winter months at LAT 23 ° S, the production of Vitamin D was much lower and started only after 10 am. The presence of cloudiness significantly impaired the formation of Vitamin D in both latitudes, even in summer months. During the warmer months of November, December and January 2012/13, there was a reduction in the efficiency of vitamin D production, mainly in LAT 23°S, in accordance with high cloud weather reports in the period. The experiment was repeated in 2014/15, when there was less cloudiness, showing significantly higher levels of vitamin D in LAT 23°S. In conclusion, latitude, season, time of day, incidence of ultraviolet B radiation and cloudiness strongly influenced Vitamin D photoconversion in vitro, outlining important regional differences. In a continental country like Brazil, this should reflect in population mean plasma 25(OH)D concentrations, suggesting that sun exposure recommendations should be particularized according to geographical conditions.